Expectations of doctoral students in the field of medicine and health sciences towards a graduate school: an online cross-sectional survey in Germany - Stock-Schröer, Beate; Lange, Silke (Frontiers in Medicine, 2024)
The doctoral thesis in medicine is a special case, as it is usually started during the course of study and the students have no experience of scientific work. , whereas in other disciplines the doctorate is completed after a successful bachelor's and master's thesis. This lack of scientific training is often criticised,, and the quality of doctoral theses in medicine is considered to be lowlow. In order In order toto increase the quality of doctoral theses and also the successful completion rate, a structured doctoral programme can provide the appropriate support. For the planned establishment of a graduate school with a thematic focus on CIM, tThese results provide important information on how the programme curriculum in the graduate school should be designed. The Not only can the time and place of the programme be adapted to the needs of the participants, but also the focus of the content depending on the degree programme, previous education and topic of the doctoral thesisNnext steps will be to evaluate the preliminary curriculum in order to develop a curriculum following the six-steps approach of Kern..